In vitro oxidant effects of D-glucosamine reduced adhesion and biofilm formation of Staphylococcus epidermidis - Aiassa, Virginia (2012)
Staphylococcus epidermidis is a common pathogen in medical device-associated infections. Its major pathogenic factor is the ability to form adherent biofilms. In this work three strains of S. epidermidis isolated from infected catheters was chosen with the objective to investigate the effect of D-glucosamine (D-Glu) on reactive oxygen species (ROS) production, adhesion and biofilm formation. We used the assay of chemiluminescence and nitroblue tetrazolium reduction to determinate the ROS production by planktonic S. epidermidis and microtiter plate assay to quantify in vitro biofilm formation. D-Glu generated a dose-dependent increase in ROS in planktonic cells with maximum stimuli at a concentration of 0.05 mM, and reduced the adhesion and biofilm formation. Whereas, glucose showed an anti-oxidative stress action and promoted the adhesion and growth of biofilm. This study suggests a potential application of D-Glu against infections associated with indwelling medical devices, since the oxidative stress caused by this hexosamine in planktonic S. epidermidis contributed to reduce the biofilm formation.